2021
DOI: 10.1182/bloodadvances.2021005509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CMV reactivation on relapse of acute myeloid leukemia after HCT is dependent on disease stage and ATG

Abstract: Cytomegalovirus (CMV) reactivation is a frequent complication after allogeneic hematopoietic cell transplantation (HCT), whose impact on clinical outcome, in particular on leukemic relapse is controversial. We retrospectively analyzed 687 HCT recipients with acute myeloid leukemia (AML) and ciclosporin-based immunosuppression to better understand the differential impact of CMV on transplant outcomes depending on AML disease stage and in-vivo T-cell depletion with anti-thymocyte globulin (ATG). Without ATG, CMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…On the other hand, a multicenter study showed that the incidence of CMV viremia was lower in non-T-cell depleted haplo-HSCT ALL patients ( Nagler et al., 2021 ). An interesting study found that the administration of ATG abrogated relapse protection following CMV reactivation in AML patients which we previously discussed ( Turki et al., 2022 ). In our study, only I-II aGVHD was linked to a significantly high incidence of CMV infection in univariate analysis.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, a multicenter study showed that the incidence of CMV viremia was lower in non-T-cell depleted haplo-HSCT ALL patients ( Nagler et al., 2021 ). An interesting study found that the administration of ATG abrogated relapse protection following CMV reactivation in AML patients which we previously discussed ( Turki et al., 2022 ). In our study, only I-II aGVHD was linked to a significantly high incidence of CMV infection in univariate analysis.…”
Section: Discussionmentioning
confidence: 79%
“…The interplay between CMV infection and primary disease relapse in patients with hematological malignancies after allo-HSCT has been an area of interest and controversy for several years. Increased evidence and our recent meta-analysis ( 20 ) implied that CMV reactivation is associated with a decreased risk of leukemia relapse in AML patients ( 21 25 ), although registry data from both the EBMT ( 26 ) and the CIBMTR ( 27 ) do not support the protective effect of CMV serology or reactivation against relapse.…”
Section: Introductionmentioning
confidence: 96%
“…Our study has several limitations due to its retrospective design, small sample size, and relatively short follow-up duration. Although CMV reactivation is a signi cant contributor to non-relapse mortality in allo-HSCT, numerous studies have also highlighted a protective aspect of CMV reactivation against relapse in AML and ALL (37)(38)(39). Owing to the small cohort and limited follow-up, we could not evaluate the protective effect of CMV reactivation against relapse.…”
Section: Discussionmentioning
confidence: 96%